On the jackson theorem for periodic functions in spaces with integral metric - Pichugov, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We consider the approximation of periodic functions by trigonometric polynomials in metric (not normed) spaces that are generalizations of the spaces L p , 0 < p < 1, and L 0. In particular, we prove the multidimensional Jackson theorem in L p (T m ), 0 < p < 1.